LA VALORACIÓN PROBATORIA EN EL TIPO PENAL FEMICIDIO - Navas Pazmiño, Juan Bladimir (2019)
In this research a critical, juridical and doctrinal analysis was carried out on how the elements of the penal type of femicide are valued in relation to the test provided by the procedural subjects in each particular case. For this, an analysis both of the scientific problems were established as the test and the means of proofs that our criminal procedure system allows and the clarification of why the material test is not considered as a means of proof. The femicide and its elements were analized as well because it was necessary to establish how this penal type is structured in our Código Orgánico Integral Penal. In addition, it was analyzed how the evidentiary valuation inferred on the judges of penal guarantees when they issued sentence either condemning or ratifying innocence. For the development of this research, the analytical, descriptive and inductive method was used. It was analyzed in a detailed way the fundamental aspects of the investigated problem allowing to describe the qualities and characteristics of the problem and this is based on the study of the problem in a particular way and then to establish conclusions and recommendations. It was possible to establish that the test is the most important of a criminal process because the procedural subjects are the responsible to generate the same to test each of the theories of the case raised in trial hearing. Within the investigation it could be pointed out that the Ecuadorian legislator made blunders at the time of legislating the penal type with it was used a bad legislative penal technique to include it within the range of crimes. Another problem found is the difficulty of proving the term power relationship, where the courts of penal guarantees do not have a clear interpretation of what proof is needed to have this normative element tested. Arriving to establish with this investigation that the relation of power is proven when within the evidentiary acquis there are complaints, text messages, messages in social networks between the passive subject and the active subject all this prior to the commit a crime, where violence, insults, cruel treatment can be specified. And that the testimonies of people nearby to the victim also serve to demonstrate the existence of power relations because in most cases the sons, daughters, mother, father, siblings are the main observers of these violence and are the first called to stop the circle of violence that ends with the death of the victim called femicide.